Penerapan WASH sebagai Langkah Awal Pencegahan Penyakit di Desa Borisallo Kabupaten Gowa - Nurul Hikmah Baharuddin; Gusnawati Gusnawati (Idea Pengabdian Masyarakat, 2021)
The application of WASH (Clean Water, Sanitation and Hygiene) is one of the first steps from infection prevention to improve and maintain mental and social welfare. The prevalence of airborne diseases can be reduced through the implementation of three main WASH practices. Based on BPS data, 71,17% is the proportion of the population that has access to proper and sustainable sanitation services in rural areas. This shows that rural areas have not been fully able to access good and safe sanitation services. The purpose of this service is to provide knowledge and understanding of the community through education and counseling about the importance of implementing clean water, sanitation and hygiene practices. method of service through counseling and education to the community. As a result of this service, there was an increase in knowledge and understanding of the community regarding the importance of implementing Clean Water, Sanitation and Hygiene (WASH). The conclusion of this service is the importance of providing education to the community regarding the implementation of WASH, so that people can independently carry out WASH.